2015
DOI: 10.3344/kjp.2015.28.4.265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Status on the Postoperative Perception of Pain

Abstract: BackgroundPostoperative (PO) pain interferes with the recovery and mobilization of the surgical patients. The impact of the educational status has not been studied adequately up to now.MethodsThis prospective study involved 400 consecutive general surgery patients. Various factors known to be associated with the perception of pain including the educational status were recorded as was the preoperative and postoperative pain and the analgesia requirements for the 1st PO week. Based on the educational status, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
2
23
0
4
Order By: Relevance
“…Little is available in the literature regarding the impact of literacy status on the level of postoperative pain. A study from Greece found out that those with the junior level of educational status experienced more intense pain compared with patients with a higher educational status [54]. The authors concluded that the low educational status is associated with poor understanding of preoperative information, which in turn might cause anxiety, depression, and suboptimal use of analgesia [54].…”
Section: Discussionmentioning
confidence: 99%
“…Little is available in the literature regarding the impact of literacy status on the level of postoperative pain. A study from Greece found out that those with the junior level of educational status experienced more intense pain compared with patients with a higher educational status [54]. The authors concluded that the low educational status is associated with poor understanding of preoperative information, which in turn might cause anxiety, depression, and suboptimal use of analgesia [54].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, preoperative psychological status and anxiety level may contribute to pain perception in patients. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The association between the education status of the patient and analgesic usage is not significant, research conducted by Wakefield et al and Platts-Mills et al [1,16] showed that patients of lower education were found to experience more pain than patients of higher education, however the education level of the patient does not depend on the type of the analgesic. [17] Thus, this justifies insignificant association between the education attainment of the patient and analgesic usage.…”
Section: Discussionmentioning
confidence: 99%